Adverse reactions to cosmetic products and the Notification System in Health Surveillance: a survey - Gisele Huf; Priscila da Nobrega Rito; Rosaura de Farias Presgrave; Maria Helena Simões Villas Bôas (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
INTRODUCTION: This paper is part of a study that investigates the quality of cosmetic products and evaluates the cosmetic surveillance system. OBJECTIVE: This study presents the results of a research that aimed to describe the point of view of the population in terms of the prevalence of Adverse Reactions (AR) and information about the surveillance system. METHODS: A structured questionnaire was applied to a random sample of 200 people from the administrative staff of the Municipal Guard of Rio de Janeiro. RESULTS: 38% of the participants declared AR to some cosmetic product used in the past two years. CONCLUSION: To our knowledge, this is an unpublished study in Brazil, which presents results regarding the estimated prevalence of AR similarly to international studies.